Queering drag redefining the discourse of gender-bending - Heller, Meredith (Indiana University Press, 2020)
"Theatrical gender-bending, also called drag, is a popular form of entertainment and a subject of scholarly study. However, most drag studies do not question the standard words and ideas used to convey this performance genre. Drawing on a rich body of archival and ethnographic research, Meredith Heller illuminates diverse examples of theatrical gender-bending: male impersonation in variety and vaudeville (1860-1920); the "sexless" gender-bending of El Teatro Campesino (1960-1980); queer butch acts performed by black nightclub singers, such as Stormé DeLarverie, instigator of the Stonewall riots (1910-1970); and the range of acts that compose contemporary drag king shows. Heller highlights how, in each case, standard drag discourses do not sufficiently capture the complexity of performers' intents and methods, nor do they provide a strong enough foundation for holistically evaluating the impact of this work. Queering Drag offers redefinition of the genre centralized in the performer's construction and presentation of a "queer" version of hegemonic identity, and it models a new set of tools for analyzing drag as a process of intents and methods enacted to effect specific goals. This new drag discourse not only allows for more complete and accurate descriptions of drag acts, but it also facilitates more ethical discussions about the bodies, identities, and products of drag performers." -- Provided by publisher